Analysis of 4C Skills (Critical Thinking, Creativity and Innovation, Collaboration, and Communication) of Physics Education Students In Facing the Industrial Revolution 4.0 - Ulil Azmi; Safrijal; Mulia Rahmi (Postgraduate, University of Mataram, 2024)
This research is a qualitative research with a case study design. The instruments used will be prepared based on the indicators of each 4C skill. The data collected will be analyzed through the stages of data reduction, data presentation and conclusions. The research results show students' critical thinking skills on indicator 1 reasoning have an achievement percentage of 34%; indicator 2 thinking as hypothesis testing has an achievement percentage of 47%; indicator 3 analyzing arguments has an achievement percentage of 49%; indicator 4 analysis of possibilities and uncertainties has a percentage of 68% and indicator 5 problem solving and decision making has a percentage of 73%. The results of students' creative and innovative thinking abilities on indicator 1 of fluency thinking skills have an achievement percentage of 28%; indicator 2 elaboration skill has an achievement percentage of 52%; indicator 3 of flexible thinking skills (flexibility) has an achievement percentage of 26%; and indicator 4 Original thinking skills (originality) has a percentage of 17%. The results of student collaboration skills in indicator 1 contributed to the percentage of achievement of 49%; indicator 2 time management has an achievement percentage of 54%; indicator 3focus on taskhas an achievement percentage of 63%; indicator 4 working with other people has a percentage of 71%; and indicator 5 responsibility has a percentage of 67%.